"I find this really entertaining" – first look of the relationship between vocational school students and various media. Issue 2 (2nd February 2022) - Meriläinen, Niina
Abstract : Purpose: The purpose of this paper is to study how young vocational school students in Finland frame themselves and their participation in society and whether they are seen in various media. The explorative research, with n = 213 vocational school and prepatory VALMA students as co-researchers, tells us that young vocational school students use value framing to create understandings of themselves as participants in society and in media. The purpose is this to present the breadth of their thinking and to draw conclusions from the empirical data produced solely by the co-researchers. Design/methodology/approach: Explorative multidisciplinary research was done as co-research with n = 213 vocational school students in Finland. Research includes theoretical background and focuses on empirical qualitative data to further illustrate the explorative nature and results of the study. Findings: The findings of the explorative co-research tell us that young vocational school students use value framing to create understandings of themselves as participants in society and in media. Co-researchers view themselves as missing in traditional media but find freedom on social media. Content from various media is viewed as reliable and trustworthy but also as problematic propaganda based on personal value framing. The relationship with traditional print media is strained because young people feel that media has othered them and continues to frame them negatively. While they look for that entertaining content across the media spectrum, bullying is an ever-present concern. Research limitations/implications: This study focused only on vocational school students in Finland. A broader sample of young people, or of minorities, could produce profound results on media literacy, relationships and power relations in the society. Also, framings of the various international media would provide content for analysis. More profound analysis of the data shall be done in the next phase of the research. Practical implications: Study time was limited. More in-depth study will follow. Implications to future research, media consumption and framing should be done with a larger group of researchers and youth. Social implications: Social implications towards framing of youth in various media and the transfer of these framing as knowledge in larger society. This includes notions of power of various actors in media and in society at large. Originality/value: Multidisciplinary explorative co-research on the topic is largely missing from academia. Additionally, the voices of those in the fringes of society is muted, whilst also those youth studying the vocational schools.